2019
DOI: 10.3390/app9235051
|View full text |Cite
|
Sign up to set email alerts
|

The Average Coding Length of Huffman Coding Based Signal Processing and Its Application in Fault Severity Recognition

Abstract: The transient impact components in vibration signal, which are the major information for bearing fault severity recognition, are often interfered with by ambient noise. Meanwhile, for bearing fault severity recognition, the frequency band selection methods which are employed to pre-process the contaminated vibration signal only select the partial frequency band of the vibration signal and cause information loss of other frequency band. Aiming at this issue, this paper proposes a novel fault severity recognitio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…93 A frequency matching linear transform technique is reported for bearing fault detection under variable rotating speeds 94 and Huffman coding technique is also used to identify bearing defect severity. 95…”
Section: Decision Tree Random Forest Ensemble Modelmentioning
confidence: 99%
“…93 A frequency matching linear transform technique is reported for bearing fault detection under variable rotating speeds 94 and Huffman coding technique is also used to identify bearing defect severity. 95…”
Section: Decision Tree Random Forest Ensemble Modelmentioning
confidence: 99%
“…In the first paper, Duan et al [39] improved the fault detection rate of a general rolling bearing by combining the local mean decomposition (LMD) and the ratio correction methods. Then, Cui et al [40] discussed the diagnosis of multiple defects in a rolling bearing via vibration analysis; Shi et al [41] reported a frequency matching linear transform technique for bearing fault detection under variable rotating speeds; moreover, Yin et al [42] proposed a Huffman coding technique to identify bearing defect severity. By what follows, artificially intelligent techniques, including ensemble learning [43] and deep learning [44,45] were developed to detect bearing faults.…”
Section: Contentmentioning
confidence: 99%
“…It is found that Huffman coding can effectively reduce the noise of the vibration signal of the rotor equipment and enhance the impact characteristics of the vibration signal in our previous study. 35 Considering that some effective feature information will be lost in the preprocessing of vibration signal, we try to combine Huffman coding with CNN, and conduct Huffman coding on the data stream during the CNN feature extraction process. In view of CNN's weak ability to identify unknown test samples, we further enhanced CNN's ability to describe normal data by increasing the distribution difference between classes of known training data to isolate the characteristic space of normal data.…”
Section: Introductionmentioning
confidence: 99%